The effectiveness of 60Co gamma-ray exposure to the reproductive systems of rat (Rattus argentiventer) as sterile male technique (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sutapa GN, Supartha IW, Wijaya IN, Puja IK, Syaifudin M. 2020. The effectiveness of 60Co gamma ray exposure to the reproductive systems of rat (Rattus argentiventer) as sterile male technique. Biodiversitas 21: 3805-3810. Various strategies have been implemented to control pests, however, these do not able to reduce rat attacks on rice plants. Therefore, the sterile male technique (SMT) using 60Co gamma radiation was introduced. A group of rats (Rattus argentiventer) of 2 months age were irradiated with 1-6 Gy doses (dose rate of 99.5631 cGy/min) and the quantity, morphology, and viability of spermatozoa of rats were assessed with standard procedures. The results showed that the concentration of spermatozoa was decreased with increasing radiation doses where for lower than 4 Gy were categorized as normal (>20 million/mL). The morphology of spermatozoa also decreased with increasing radiation dose where under 3 Gy were in normal (> 50%). Spermatozoa viability was also decreased where for doses 1 and 2 Gy were categorized as normal. Statistical analysis showed a significant difference (p
Keywords: 60Co gamma radiation, rat pest, reproductive system, sterile male technique